2021
DOI: 10.3390/rel12121084
|View full text |Cite
|
Sign up to set email alerts
|

Framing of Abortion and Church-State Relations in Russian Orthodox Online Portals

Abstract: Over the past two decades, clerics in the Russian Orthodox Church have found a new outlet for morality policy discussions: news portals, blogs, and other sites that comprise a virtual public sphere of Russian Orthodox online media. One prominent issue discussed herein is abortion in Russia, a subject that has spawned debates about possible regulation and prevention measures. This article analyzes statements regarding abortion made by clerics and others serving in the Russian Orthodox Church via Russian Orthodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…A prior analysis of clerics and others serving in the ROC via Russian Orthodox online news portals (Hill, 2021) employed a morality frame typology based on Mucciaroni (2011) and adapted to the Russian case. The results showed that rational-instrumental frames dominated; however, unlike Mucciaroni’s (2011) findings, procedural frames lagged behind religious arguments by a significant margin.…”
Section: Theoretical Approaches To Morality Framingmentioning
confidence: 99%
See 4 more Smart Citations
“…A prior analysis of clerics and others serving in the ROC via Russian Orthodox online news portals (Hill, 2021) employed a morality frame typology based on Mucciaroni (2011) and adapted to the Russian case. The results showed that rational-instrumental frames dominated; however, unlike Mucciaroni’s (2011) findings, procedural frames lagged behind religious arguments by a significant margin.…”
Section: Theoretical Approaches To Morality Framingmentioning
confidence: 99%
“…The results showed that rational-instrumental frames dominated; however, unlike Mucciaroni’s (2011) findings, procedural frames lagged behind religious arguments by a significant margin. In addition, four procedural sub-frames based on Stoeckl’s (2018) models of church-state relations were identified: ‘symphony’ frames promoting church-state partnerships, ‘affinity’ frames expressing approval of state initiatives, ‘disillusionment’ frames expressing frustration with the state’s performance, and ‘disestablishment’ frames portraying the state as opposed to or threatening the general population’s well-being (Hill, 2021: 6, 7).…”
Section: Theoretical Approaches To Morality Framingmentioning
confidence: 99%
See 3 more Smart Citations